Resistless Nanoimprinting in Metal for Plasmonic Nanostructures. Issue 22 (18th April 2013) - Varghese, Leo T.; Fan, Li; Xuan, Yi; Tansarawiput, Chookiat; Kim, Sangsik; Qi, Minghao
Abstract Metal nanostructures are the main building blocks of metamaterials and plasmonics which show many extraordinary properties not existing in nature. A simple and widely applicable method that can directly pattern metals with silicon molds without the need of resists, using pressures of <4 MPa and temperatures of 25–150 °C is reported. Three‐dimensional structures with smooth and vertical sidewalls, down to sub‐10 nm resolution, are generated in silver and gold films in a single patterning step. Using this nanopatterning scheme, large‐scale vivid images through extraordinary optical transmission and strong surface‐enhanced Raman scattering substrates are realized. Resistless nanoimprinting in metal (RNIM) is a new class of metal patterning that allows plasmonic nanostructures to be fabricated quickly, repeatedly, and at a low‐cost.